Comparison of the bronchodilator and cardiovascular actions of salbutamol, isoprenaline and orciprenaline in guinea-pigs and dogs - Daly, M. J. (1971)
1. Bronchodilator and cardiovascular actions of salbutamol and isoprenaline have been compared in guinea-pigs and dogs. Orciprenaline was also included in some experiments. 2. All three drugs antagonized acetylcholine-induced increases in pulmonary resistance. In addition they increased heart rate and decreased arterial blood pressure. 3. Compared with isoprenaline, salbutamol has relatively stronger actions on bronchial and vascular β-adrenoceptors than on cardiac β-adrenoceptors, on which its action is very weak. In contrast, orciprenaline has similar potencies on β-adrenoceptors in these three tissues. 4. The positive chronotropic potency of intravenously or orally administered salbutamol was increased in conscious dogs. These heart rate responses to salbutamol were probably mainly reflex in origin. 5. Salbutamol and orciprenaline were both longer acting than isoprenaline. 6. The results support the idea of two distinct groups of β-adrenoceptors. Salbutamol differentiates between bronchial and vascular β(2)-adrenoceptors on the one hand and cardiac β(1)-adrenoceptors on the other. Isoprenaline and orciprenaline do not differentiate between β(1)- and β(2)-adrenoceptors.